2021
DOI: 10.17221/419/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat root exudates on bacterial communities in the rhizosphere of watermelon

Abstract: In this study, we investigated the effects of wheat root exudates on soil bacterial communities in the watermelon rhizosphere using quantitative PCR and Illumina MiSeq sequencing. The qPCR results showed that wheat root exudates significantly increased the abundance of total bacteria, Pseudomonas, Bacillus and Streptomyces spp. Illumina MiSeq sequencing results showed that wheat root exudates significantly changed the bacterial community structure and composition. These results indicated that plant root exudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“… 59 Therefore, the composition of root-associated microbial community (i.e., in the rhizosphere) is strictly linked with the composition of root exudates of a plant, and any change in root exudation could potentially alter the soil biodiversity in the close vicinity. 60–62 Despite the obvious differences in metabolic profile in the soils of two maize cultivars at each growth stage, similar to the results of most of the previous studies conducted on cry1Ah insecticidal maize, 34 , 63 , 64 , 65 no difference in rhizosphere bacterial community was found in our study. Interestingly, the relative abundances of some bacterial OTUs were yet correlated with the altered metabolites in transgenic maize.…”
Section: Discussionsupporting
confidence: 89%
“… 59 Therefore, the composition of root-associated microbial community (i.e., in the rhizosphere) is strictly linked with the composition of root exudates of a plant, and any change in root exudation could potentially alter the soil biodiversity in the close vicinity. 60–62 Despite the obvious differences in metabolic profile in the soils of two maize cultivars at each growth stage, similar to the results of most of the previous studies conducted on cry1Ah insecticidal maize, 34 , 63 , 64 , 65 no difference in rhizosphere bacterial community was found in our study. Interestingly, the relative abundances of some bacterial OTUs were yet correlated with the altered metabolites in transgenic maize.…”
Section: Discussionsupporting
confidence: 89%
“…Fungi directly and positively affected root diameter. Studies have confirmed that the mycelial network of AM fungi expand the space of mineral and water absorption in root system, which promotes the growth and component accumulation of medicinal plants (Sun et al, 2021). G+ bacteria directly and negatively affected root branching number, rosmarinic acid and salvianolic acid B contents, but G-bacteria only directly and negatively affected rosmarinic acid content.…”
Section: Effect Of Rhizosphere Soil Physicochemical Properties and Mi...mentioning
confidence: 89%
“…Plant root distribution can influence soil physicochemical properties such as substrates and pH along soil profiles (Pietri and Brookes, 2008). Plant root systems are the main medium for exudates into rhizosphere soil, and root exudates can change the physicochemical properties and microbial composition of the rhizosphere soil to a plant's benefit (Bakker et al, 2018;Shi et al, 2021). Zhang et al (2022) reported that ginseng rhizosphere bacterial community structure is affected by genotype, and there is a correlation between ginseng genotypes and the bacterial population structure.…”
Section: Effect Of Genotype and Climatic Factors On Growth And Active...mentioning
confidence: 99%
“…Six genera, including Sphigomonas, Pedobacter, Parablastomonas, Paracoccus, Pir4_lineage, and Nocardioides, were identified as biomarkers in good-quality samples. These six biomarkers for good-quality samples were reported to be related to agriculture rhizosphere soil [56][57][58][59][60][61]. Three genera, Sphigomonas, Pedobacter, and Nocardioides, were also identified as core microbiota in healthy samples in the Kusstatscher et al ( 2019) study [9].…”
Section: Integrated Taxonomic Analysis Identifies Generalizable Taxa ...mentioning
confidence: 91%